2018
DOI: 10.1080/14656566.2018.1473378
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin for the treatment of type 2 diabetes: a comparison between Japanese and non-Japanese patients

Abstract: Canagliflozin, a sodium-glucose co-transporter-2 (SGLT2) inhibitor, improves various cardiometabolic parameters. Although canagliflozin was originally discovered in Japan, no comprehensive summary of its effects in Japanese patients has been reported. As differences exist in the pathologic features of diabetes between Japanese and non-Japanese populations, it is important to consolidate Japanese data for canagliflozin. Areas covered: The authors summarize Japanese clinical trial and post-marketing surveillance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 93 publications
0
20
0
Order By: Relevance
“…Owing to the differences in their mechanisms of action, teneligliptin and canagliflozin act in a complementary manner. Body weight management is important for maintaining good long-term glycemic control with DPP-4 inhibitors [ 92 , 93 ], and the SGLT2 inhibitor canagliflozin reduces not only blood glucose but also body weight [ 94 ]; thus, the FDC of teneligliptin/canagliflozin also represents a useful therapeutic option for T2DM patients, with additional benefits such as adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the differences in their mechanisms of action, teneligliptin and canagliflozin act in a complementary manner. Body weight management is important for maintaining good long-term glycemic control with DPP-4 inhibitors [ 92 , 93 ], and the SGLT2 inhibitor canagliflozin reduces not only blood glucose but also body weight [ 94 ]; thus, the FDC of teneligliptin/canagliflozin also represents a useful therapeutic option for T2DM patients, with additional benefits such as adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are limited data for ipragliflozin outside of Asia, the effects of other SGLT2 inhibitors (e.g., canagliflozin) have been studied in detail. For example, a recent review by Inagaki et al . concluded that canagliflozin had similar efficacy and safety profiles in Japanese and non‐Japanese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among clinical trials, post hoc analysis of the EMPA-REG and CANVAS clinical trials show that empagliflozin had more cardiovascular benefits in Asians than canagliflozin (in contrast, African Americans had greater cardiovascular benefits with canagliflozin) (257). However, in multiple clinical studies, and notwithstanding a theoretical advantage of glucose-lowering in Asians (who may have more of a b-cell impairment), there were similar clinical efficacy and safety data results with sodium-glucose cotransporter-2 inhibitor (SGLT2i) use among Asians, Caucasians, African Americans/Blacks, and other racial groups (258)(259)(260)(261)(262)(263). In a pharmacogenomics study involving Taiwanese patients with T2D, there were 45 gene variants associated with therapeutic responses to dipeptidyl peptidase-4 inhibitors, with an affirmation that b-cell dysfunction plays more of an etiologic role than insulin resistance in Asians (264).…”
Section: Diabetes Carementioning
confidence: 99%